Implementation of Khan Academy Based Learning Media to Improve Numerical Literacy Skills - Jumelan Jumelan; Arif Budi Wurianto; Muhammad Syaifudin (LP. Ma'arif Janggan Magetan, 2026)
Numeracy skills are fundamental competencies in primary education to prepare students for the demands of the digital era. However, numeracy achievement in several elementary schools still requires strengthening through innovative digital learning media. This study aims to (1) determine the effectiveness of Khan Academy–based learning media in improving numeracy skills among elementary school students in Pacitan Regency, and (2) analyze changes in numerical literacy following its implementation. A quantitative approach supported by descriptive data was employed. Data were collected through pre-tests, post-tests, and interviews with teachers and students regarding their perceptions of Khan Academy. Quantitative data were analyzed using the Paired Sample t-Test to compare pre-test and post-test results, while qualitative data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings indicate a significant improvement in students’ numeracy performance. The average score increased from 60.4 to 78.2, with an average gain of 17.8 points. Statistical analysis revealed a t-value of –60.603 with p < 0.05, indicating a significant difference between pre-test and post-test scores. Students also demonstrated high engagement in interactive exercises, along with increased independence and conceptual understanding. In conclusion, the use of Khan Academy as a digital learning medium effectively enhances numeracy skills in primary education and serves as an innovative solution to support technology-based learning in the digital era.